Proinflammatory Cytokines, Enolase and S-100 as Early Biochemical Indicators of Hypoxic-Ischemic Encephalopathy Following Perinatal Asphyxia in Newborns - Verónica Chaparro-Huerta; Mario Eduardo Flores-Soto; Mario Ernesto Merin Sigala; Juan Carlos Barrera de León; María de Lourdes Lemus-Varela; Blanca Miriam de Guadalupe Torres-Mendoza; Carlos Beas-Zárate (Elsevier, 2017)
Estimation of the neurological prognosis of infants suffering from perinatal asphyxia and signs of hypoxic-ischemic encephalopathy is of great clinical importance; however, it remains difficult to satisfactorily assess these signs with current standard medical practices. Prognoses are typically based on data obtained from clinical examinations and neurological tests, such as electroencephalography (EEG) and neuroimaging, but their sensitivities and specificities are far from optimal, and they do not always reliably predict future neurological sequelae. In an attempt to improve prognostic estimates, neurological research envisaged various biochemical markers detectable in the umbilical cord blood of newborns (NB). Few studies examining these biochemical factors in the whole blood of newborns exist. Thus, the aim of this study was to determine the expression and concentrations of proinflammatory cytokines (TNF-α, IL-1β and IL-6) and specific CNS enzymes (S-100 and enolase) in infants with perinatal asphyxia. These data were compared between the affected infants and controls and were related to the degree of HIE to determine their utilities as biochemical markers for early diagnosis and prognosis. Methods: The levels of the proinflammatory cytokines and enzymes were measured by enzyme-linked immunosorbent assay (ELISA) and Reverse Transcription polymerase chain reaction (RT-PCR). Results: The expression and serum levels of the proinflammatory cytokines, enolase and S-100 were significantly increased in the children with asphyxia compared with the controls. Conclusion: The role of cytokines after hypoxic-ischemic insult has been determined in studies of transgenic mice that support the use of these molecules as candidate biomarkers. Similarly, S-100 and enolase are considered promising candidates because these markers have been correlated with tissue damage in different experimental models.